Preparing the U.S. Army for Homeland Security Concepts, Issues, and Options - Larson, Eric V. (RAND Corporation, 2001)
Homeland security encompasses five distinct missions: domestic preparednessand civil support in case of attacks on civilians, continuity of government, continuity ofmilitary operations, border and coastal defense, and national missile defense. This reportextensively details four of those mission areas (national missile defense having beencovered in great detail elsewhere). The authors define homeland security and its missionareas, provide a methodology for assessing homeland security response options, and reviewrelevant trend data for each mission area. They also assess the adequacy of the doctrine,organizations, training, leadership, materiel, and soldier systems and provide illustrativescenarios to help clarify Army planning priorities. The report concludes with options andrecommendations for developing more cost-effective programs and recommends a planningframework that can facilitate planning to meet homeland security needs.